BENTUK DAN FUNGSI KONJUNGSI DALAM NOVEL â€œA STOLEN LIFEâ€ OLEH JAYCEE DUGARD (SEBUAH ANALISIS SINTAKSIS) - ASTUTI, ASTUTI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled â€œForms and Functions of Conjunction In A Novel â€œA Stolen Lifeâ€ by Jaycee Dugard. In the aspect of forms, conjunction is devided into Coordinative conjunction, Subordinative conjunction and correlative conjunction. On functional grounds, conjunction can distinguish between coordinating conjunctions (coordinators) and subordinating conjunctions (subordinators). Coordinators function as linkers between sentences, clauses, and phrases. Subordinators introduce subclauses, that is clauses functioning as constituents of sentences or phrases. This research is an attempt to identify, classify, and analyze the conjunction in the novel in terms of the forms and functions. This is a descriptive study that used the consept of Aarts and Aarts (1982). The result of this research shows that, the coordinate conjunctions found are and, but, or, and for.Tthe subordinate conjunctions found are if, while, because, unless, that, before, whether, since, yet, until, as, than, so, although, however, whenever, as soon as, as if, as well as, and such as. The correlative conjunctions found are whetherâ€¦or and eitherâ€¦or. The functions of conjunction found are connecters between two words in one a sentence, two phrases in one sentence, clauses and clauses, clauses and phrases, and phares and clauses. Keywords:Â Forms and Functions, Conjunction, A Stolen Life